(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article analyzes the thematic and artistic peculiarities and creative skills of the talented akyn Maraltay Raiymbekuly, bright representative of Kazakh poetry at the beginning of 90s. The author of the article thoroughly and scientifically examined the earlier not investigated aspects of his poetry. Poetry is the art of words, a sample of artistic skill, which has no equal. Besides, it is the opportunity to show the public and social changes through words, the realities of life, to give the public consciousness the art and aesthetic content. With all this, the article along with the peculiarities of modern Kazakh poetry analyzes the poetic creativity of Maraltay Raiymbekuly, who takes his rightful place in the galaxy of talented poets. Drawing attention to the thematic diversity of the akyn’s creativity, the author gives special focus on some of the topics that reveal the versatility of the artist.